Expression of bone-specific genes and proteins in human fetal osteoblast cell line (hfob 1.19) treated with semi-purified fraction of quercus infectoria - Hapidin, Hermizi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
The study aim to investigate the effect of established Quercus infectoria (QI) semi-purified fractions (Qlsm-F) and combination of established Qlsm-F fraction with readily available osteoporotic drug (pamidronate) on proliferation, differentiation and mineralisation of osteoblast as well as to delineate the molecular mechanism of Qlsm-F that enhanced bone formation by employing hFOB 1.19 cell model. A total of 13 Qlsm-F were isolated by chromatographic technique and tested in series of bio-guided assay by MTT assay to determine the most potent fraction. Three most potent fractions; Fraction A (FA), Fraction B (FB) and Fraction C (FC) were used throughout this study. Polyphenolic content of each Qlsm-F were identified by LCMS. The cells were treated on day 1, day 3 and day 7 for assessments of mineralisation by Alizarin Red S staining [calcium (Ca) depositions] and von Kossa staining [phosphate (P) depositions] and also evaluation of cellular morphology by using microscope. Detailed assessment of bone specific markers were conducted by RT-PCR, western blot and immunofluorescence staining. The LCMS analysis of each FA, FB and FC reveals that each fraction consists of mainly polyphenolic compounds (gallic acid, digallate, ellagic acid, syringic acid and theogallin). The mineral deposition per viable cell increases with treatment of FA, FB and FC as well as combined treatment of FA, FB and FC with pamidronate on hFOB1 .19 cells in a time-dependent manner. Interestingly, from day 3 until day 7; quantification of investigated bone specific genes (Runx2, Osx, BMP-2, BSPll, BGLAP, and TGF-J31) and proteins (Runx2, Osx and BSPll) on hFOB1.19 cells were highest in cells treated with combined treatment of FA, FB and FC with pamidronate and at peak in cells treated with combined treatment of FC with pamidronate compared to hFOB 1.19 cells treated with single individual treatment. Protein analysis results • were consistent with investigation of immunofluorescence staining. Therefore, these finding demonstrated that polyphenols presence in each FA, FB and FC enhanced mineral deposition along with expression of investigated bone marker as well as acknowledge the potential therapeutic effects when combining each Qlsm-F with pamidronate through increasing efficiency of pamidronate acting on osteoblast cells.